Effect of dissolved carbon dioxide on oxygen consumption in the Pacific white shrimp, Litopenaeus vannamei (Boone 1931). Issue 5 (2nd September 2016) - Furtado, Plínio S.; Valenzuela, Manuel A. J.; Badillo, Maribel A.; Gaxiola, Gabriela; Wasielesky, Wilson
Abstract: A failure in the aeration system of Litopenaeus vannamei rearing with biofloc technology can decrease the oxygen concentrations rapidly and also increase the carbon dioxide (CO2 ) concentrations at the same rate. We report here an evaluation of the effect of CO2 on the oxygen consumption of L. vannamei . We used a continuous-flow respirometer with water recirculation equipped with a digital fiber-optic oximeter. Eight juveniles of L. vannamei (12.1 ± 1. 4 g) were used in each treatment with one per respiratory chamber (0.6 L). The shrimp were exposed to six concentrations of CO2 (5, 30, 60, 95, 150, and 300 mgCO2 /L) with an acute exposure time of six hours. Upon treatment with 5–30 mgCO2 /L, we observed a consumption of oxygen of 0.233 ± 0.129 and 0.33 ± 0.072 mgO2 /g/h, respectively. Upon treatment with 60 mgCO2 /L, an increase was observed in the oxygen consumption (0.521 ± 0.098 mgO2 /g/h). Upon treatment with 95, 150, and 300 mgCO2 /L however, the shrimp decreased their oxygen consumption and lost their equilibrium. The CO2 should therefore be maintained at a maximum of 5 mgCO2 /L during shrimp rearing.